2016
DOI: 10.1021/acs.orglett.6b01022
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Iodination of the Aliphatic C–F Bond by YbI3(THF)3: Mechanistic Insight and Synthetic Utility

Abstract: A facile iodination protocol of unactivated alkyl fluorides using catalytic amounts of YbI3(THF)3 in the presence of iodotrimethylsilane as a stoichiometric fluoride trapping agent is presented. (1)H NMR spectroscopy demonstrates a two-step catalytic cycle where TMSI regenerates active YbI3(THF)3. Finally, the catalytic reaction is extended into a one-pot procedure to demonstrate a potential application of the method. Overall, the findings present a distinct strategy for C-F bond transformations in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
(13 reference statements)
1
17
1
Order By: Relevance
“…Following our previous work with fluorinated oxindoles and through serendipitous screening of reaction conditions, we found that the fluorooxindole 1 undergoes reductive defluorination in the presence of trimethylsilyl iodide (TMSI). This results in pronucleophilic C─F bond activation, which is in stark contrast to the proelectrophilic C─F bond cleavage previously reported by Hilmersson and others ( 21 , 22 ). We were able to trap the in situ generated nucleophile as the Michael addition product 3 in 76% yield ( Fig.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Following our previous work with fluorinated oxindoles and through serendipitous screening of reaction conditions, we found that the fluorooxindole 1 undergoes reductive defluorination in the presence of trimethylsilyl iodide (TMSI). This results in pronucleophilic C─F bond activation, which is in stark contrast to the proelectrophilic C─F bond cleavage previously reported by Hilmersson and others ( 21 , 22 ). We were able to trap the in situ generated nucleophile as the Michael addition product 3 in 76% yield ( Fig.…”
Section: Resultscontrasting
confidence: 78%
“…The diverse chemical space that can now be accessed through pronucleophilic and proelectrophilic C─F bond activation as well as the integration of both pathways into a one-pot procedure is highlighted with more than 65 examples. C─F bond activation with ytterbium, silicon, and lanthanide Lewis acids (4,5,12,14,18,21,22,30) and C─F bond cleavage observed in our laboratory during the synthesis and derivatization of fluorinated oxindoles, nitriles, nitromethyl ketones, as well as alkyl, benzyl and aryl fluorides (19,(39)(40)(41)(42) encouraged us to investigate whether broadly applicable, chemodivergent C─F bond cleavage using alkyl fluorides either as proelectrophiles or as pronucleophiles is possible when coupled with the generation of a stable inorganic fluoride salt. Following our previous work with fluorinated oxindoles and through serendipitous screening of reaction conditions, we found that the fluorooxindole 1 undergoes reductive defluorination in the presence of trimethylsilyl iodide (TMSI).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the syn isomer of 3 o is thermodynamically preferred over the anti isomer, and that a predominantly S N 1 pathway operates, in which a degree of ‘ion‐pairing“ between the carbocation and fluoroboronate anion may contribute to observed anti 3 o product in the reaction using syn 1 k . Both S N 1 and S N 2 pathways have been reported for related halodefluorination reactions …”
Section: Figurementioning
confidence: 51%
“…4–12 In addition, several laboratories, including ours, have been able to demonstrate carbon–fluoride bond functionalization with unactivated aliphatic substrates although the need for harsh conditions, together with low functional group tolerance and competing side reactions continue to limit the general scope in some cases. 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31…”
Section: Table 1 Optimization Of the Csp ...mentioning
confidence: 99%